Dangerous medicines: Unproven AIDS cures and counterfeit antiretroviral drugs - Amon Joseph J (BMC, 2008)
Abstract Background Increasing access to antiretroviral therapy (ART) is a critical goal endorsed by the United Nations and all of its member states. At the same time, anecdotal accounts suggest that the promotion of unproven AIDS 'cures' and remedies are widespread, and in the case of The Gambia, Iran and South Africa, have been promoted by governments directly. Although a range of legislative and regulatory measures have been adopted by some governments, and technical assistance has been provided by international agencies to address counterfeit medicines generally, the threat of counterfeit antiretroviral drugs is not being addressed. Discussion Countries, charged with fulfilling the right to health and committed to expanding access to ART must explicitly recognize their obligation to combat unproven AIDS treatments and ensure the availability of a safe and efficacious drugs supply. International donors must help support and coordinate these efforts.